Adaptation of adsorption cooling system for hot and dry climates: Use of ground water heat exchanger coupled to direct evaporative cooling tower - Kheireddine, Mohamed-Abdelbassit; Benchabane, Adel; Rouag, Amar; Mahbubul, I. M.; Arici, Muslum; Demir, Hakan; Sevindir, Mustafa Kemal (TAYLOR & FRANCIS INC, 2023)
The current study focused on the adaptation of adsorption cooling systems to hot and arid climates. A new combination is proposed to improve the performance of the direct evaporative cooler (DEC). This combined system consists in coupling Ground-Water Heat Exchanger (GWHE) with a DEC of a hybrid cooling tower. A mathematical model has been developed and validated to depict the heat and mass transfer that occurs in the DEC between the air and water, as well as between the ground and water in the geothermal heat exchanger. The key variables taken into consideration are the outdoor air temperature and the mass flow rate and the temperature of water. The effect of the inlet hot air velocity and temperature, and water mass flow rate, on the evaporated water is investigated. The findings indicate that the mathematical model of a DEC coupled to GWHE predicts optimal characteristics, leading to a reduction in the air temperature from 48 & DEG;C to 32 & DEG;C at the heat exchanger inlet of the cooling tower.
Keywords: Solar adsorption system; ground water heat exchanger; direct evaporative cooling tower; thermal analysis; hot and dry climate; TRANSIENT SEMIANALYTICAL MODEL; THERMAL DESIGN; MASS-TRANSFER; PART I; REFRIGERATION; WORKING; COOLER; Energy & Fuels; Engineering; Environmental Sciences & Ecology